WHEEL OF NAMES DAN WORDWALL UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR FIKIH (MI NURUL ARJOSARI MALANG) - Afkari, Najmi Nahdin (Muta'allim: Jurnal Pendidikan Agama Islam, 2024)
The development of the times is increasingly advancing towards convenience in all aspects, one of which is with the help of technology. The application of technology in various fields, one of which – education – makes it easier for educators and students (students and students) to learn. The use of learning media available on the Internet, such as Wheel of Names and Worldwall allows students to understand learning with a fun game. This study used qualitative methods targeting 26 grade IV students. The results showed changes in student attitudes after using Wheel of Names (spinner) and Worldwall learning media in learning. This change can be seen from student activeness and observational assessment through the following indicators: (a) student activeness in participating in teaching and learning activities, (b) asking questions about material that has not been understood, and (c) activeness in collecting assignments on time. The conclusion of this study is that the use of Worldwall media in class IV jurisprudence learning can increase student interest and motivation to learn. AbstrakPerkembangan zaman yang semakin maju ke arah kemudahan dalam segala aspek, salah satunya dengan bantuan teknologi. Penerapan teknologi dalam pelbagai bidang salah satunya—pendidikan—memudahkan pendidik maupun peserta didik (siswa dan siswi) dalam belajar. Penggunaan media pembelajaran yang tersedia di Internet, seperti Wheel of Names dan Worldwall memungkinkan peserta didik dalam memahami pembelajaran dengan suatu permainan yang menyenangkan. Penelitian ini menggunakan metode kualitatif dengan sasaran 26 siswa kelas IV. Hasil penelitian menunjukkan perubahan sikap siswa setelah menggunakan media pembelajaran Wheel of Names (spinner) dan Worldwall dalam pembelajaran. Perubahan ini terlihat dari keaktifan siswa dan penilaian observasi melalui indikator berikut: (a) keaktifan siswa dalam mengikuti kegiatan belajar mengajar, (b) bertanya tentang materi yang belum dipahami, dan (c) keaktifan dalam mengumpulkan tugas tepat waktu. Kesimpulan penelitian ini adalah penggunaan media Worldwall pada pembelajaran fikih kelas IV dapat meningkatkan minat dan motivasi belajar siswa.